PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS (STUDI PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Silvia Nur Krishna Murthi; Ahmad Subaki,; Sumardi, Sumardi (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract— This study aims to determine the effect of Sales Growth, Accounts Receivable Turnover, Inventory Turnover, Company Size and Leverage on Profitability of Food and Beverage Sector Companies listed on the Indonesia Stock Exchange (IDX). The type of data used is secondary or quantitative data. The variables studied were Sales Growth, Accounts Receivable Turnover, Inventory Turnover, Company Size and Leverage on Profitability. The sample used was 8 companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Determination of sample selection using purposive sampling and data processing method using multiple linear regression analysis. The results showed that partially the sales growth variable, accounts receivable turnover, had no significant effect on the profitability variable (ROA), the inventory turnover variable and company size had a significant negative effect on the profitability variable (ROA). While the leverage variable (DER) has a positive and significant effect on the profitability variable (ROA). Simultaneously, the variables of sales growth, accounts receivable turnover, inventory turnover, company size and leverage (DER) have a significant and significant effect on the profitability (ROA) variable. The ability of the independent variable in explaining the dependent variable can be seen from the analysis of the coefficient of determination R2 of 0.359%. This means that only 35.9% profitability (ROA) which can be explained by the variables of sales growth, receivables turnover, inventory turnover, company size and leverage (DER). While the remaining 64.1% is explained by other variables that are not included in this study. Keywords: Accounts Receivable Turnover; Company Size; Inventory Turnover; Leverage; Sales Growth